Broad-spectrum resistance to bacterial blight in rice using genome editing - Oliva, Ricardo; Ji, Chonghui; Atienza-Grande, Genelou; Huguet-Tapia, José C.; Perez-Quintero, Alvaro; Li, Ting; Eom, Joon-Seob; Li, Chenhao; Nguyen, Hanna; Liu, Bo; Auguy, Florence; Sciallano, Coline; et al. (Springer, 2019)
Bacterial blight of rice is an important disease in Asia and Africa. The pathogen,Xanthomonas oryzaepv.oryzae(Xoo), secretes one or more of six known transcription-activator-like effectors (TALes) that bind specific promoter sequences and induce, at minimum, one of the three host sucrose transporter genesSWEET11,SWEET13andSWEET14, the expression of which is required for disease susceptibility. We used CRISPR–Cas9-mediated genome editing to introduce mutations in all threeSWEETgene promoters. Editing was further informed by sequence analyses of TALe genes in 63Xoostrains, which revealed multiple TALe variants forSWEET13alleles. Mutations were also created inSWEET14, which is also targeted by two TALes from an AfricanXoolineage. A total of five promoter mutations were simultaneously introduced into the rice line Kitaake and the elite mega varieties IR64 and Ciherang-Sub1. Paddy trials showed that genome-editedSWEETpromoters endow rice lines with robust, broad-spectrum resistance.